The politics of good enough data. Developments, dilemmas and deadlocks in the production of global learning metrics. (January 2023) - Fontdevila, Clara
Abstract: The indicator framework established for the monitoring of SDG4 is unambiguous on the need to advance in the production of global learning data. However, the production of SDG4 learning metrics has been riddled with technical and political difficulties. Drawing on a combination of documentary analysis, interviews and non-participant observation, this paper reconstructs the process of negotiation of the data suppliers, statistical routines and reporting standards necessary for the production of SDG4 learning metrics. The paper thus offers insight into the mechanics of global quantification, and on the transformative impact of such processes on the agendas and relationships of partaking organizations. Highlights: With the advent of SDG4, the production of globally-comparable learning data has become an institutional priority for UIS. The production of globally comparable learning data presents technical as well as political difficulties related to the collective nature of indicator-making. The relative success of the UIS in the area of learning measurement owes much to its efforts to posit itself as an honest broker and accomodate different data sources and harmonization mehods. UIS' centrality is endangered by the existence of parallel measurement projects and an uncertain rapport with UNESCO. The production of SDG4 learning data has been shaped by a tension between the principles of in-built comparability and country ownership.